SEGMENTASI MORFOLOGI UNTUK MENGKUANTIFIKASI HASIL PEMERIKSAAN PAP SMEAR DALAM MENDETEKSI KANKER SERVIKS - Soeprapto Soeprapto; Kenty Wantri Anita (Journal of Environmental Engineering and Sustainable Technology, 2014)
ABSTRACT Currently used screening method for the early detection of cervical cancer with a Pap smear others, and Visual Inspection Acetic Acid (VIA). If the inspection indicated the existence of cervical precancerous lesions, the patients are advised to do a biopsy and colposcopy examination HPV test, because histopathologic examination to be the gold standard in the diagnosis of cancer.Pap Smear test provides several advantages: it can be done quickly and can give positive results. Malignancies can be diagnosed while still in situ stage, but there are also drawbacks, namely: only able to detect lesions that are located on the surface of the mucosa) still need to be confirmed by biopsy. Identify the possibility of the cancer cells in the Pap smear is characterized by: the shape round oval cells with different sizes, cell nuclei tend to be larger, core diskariotik, hiperkromatik and coarse chromatin. From the results of comparison testing between the cytoplasm to the nucleus of cells in samples Pap smear with a normal category get a number that is likely to stick with an average value of 32.5. Keywords : Pap Smear, Digital Image Processing, ca cervix.